Bahaya Penyalahgunaan Napza dan Rokok : The Dangers of Illicit Drugs and Cigarette Abuse - Syahrul Tuba; Yahdiana Harahap; Eva Fitri Yuanita; Reynatha CA Pangsibidang; Putri Diana Nurul Adha (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2023)
There are numerous addictive chemicals that are extremely harmful to the body and pose a problem for humanity in various parts of the world. One of them is commonly referred to as narcotics, psychotropic, and other addictive chemicals (drugs) or drugs (narcotics and dangerous drugs). The purpose of the service is to inform the public of the health risks associated with drug abuse and cigarette smoking, to persuade the public of the importance of protecting themselves and their families from drugs and cigarettes, and to demonstrate the effectiveness of government programs in eradicating drug abuse. In partnership with the National Narcotic Board (BNN) RI, 125 participants have received socialization through online presentations, as well as information counseling for early identification and anticipation of the hazards of narcotics, cigarette, and also new psychoactive substances (NPS). Through the socialization and education on the dangers of narcotics and cigarette use for this health, it can be concluded that the participants gain confidence, knowledge, and early detection of the type of New Psychoactive Substance (NPS), narcotics, and cigarettes, as well as a heightened awareness of the dangers of drug and cigarette use. So that this action can assist the government in strengthening by soliciting the public's assistance and support for BNN's efforts to break the chain of illegal drug trafficking, it is intended.